PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BANK TABUNGAN PENSIUNAN NASIONAL (BTPN) SYARIAH.Tbk CABANG BOGOR - Shintia Lusiyanti Sitorus; Paryoto (Human Capital Development, 2015)
Purpose- Aiming of this research is to findout the effect of compensation, and motivation toward the staff’s performance at Bank Tabungan Negara (BTN). Design/methology/approach- A questionaire survey to employees of Bank Tabungan Negara (BTN), Bogor Branch, the sample were 91 respondents derived by Slovin formula, within a single organization supported by interviews. Findings- Based on F-test, it is concluded that Organizational communication and Compensation simultaneously have effected the work motivation of the employee in P.T.Nexwave Jakarta. It it double checked, the result of t-test is also confirming that Organizational communication and Compensation simultaneously have effeFinally the coorelation and determinant test is applied that this is also determines that there is a real relationship among the two varibales against the work motivation of the employees in PT.Nexwave, atrongly. Research limitations-However the capacity of independent variables to influence the effect on work motivation is weaker than other variables, that are not included in this research Practical implications-The manager of human resource shall maintain the authentic information by means of available organizational communications. Additionally is is a main area to evaluate the existing compensation as it has bigger effect on work motivation. The Originality-This is done exclusively for the single company that may applicable therein